Model Regenerasi Petani Bawang Merah Di Kabupaten Solok Sumatera Barat - Alvindo Dermawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The agricultural sector requires the regeneration of human resources who are productive and have skills in farming. This study aims to describe the condition of farmers' resources and describe the regeneration model of shallot farmers in Solok Regency. This study used a survey research method with a qualitative approach to 30 shallot farmers spread across Solok Regency. The data used in the form of primary data and secondary data. The results showed that most of the shallot farmers in Solok Regency were productive farmers with an age range of 19-40 years, namely 80 percent with high school education to university education. The regeneration model of shallot farmers in Solok Regency is included in the planned model with a family approach. These results indicate the need for further deepening of understanding about youth involvement in agriculture and the regeneration of shallot farmers in Solok Regency.